Ambition Of Love Reflected In Lauren Kate's Novel Fallen (2009) : A Psychoanalytic Approach - Santi, Aisyah Pramutika; , Drs. Abdillah Nugroho, M.Hum; , Dr. Phil. Dewi Candraningrum, M. Ed (2013)
The major problem of this study is how ambition of Lucinda Price in Fallen novel (2009) based on Psychoanalytic approach. The objective of this study are to analyze the novel based on structural element and to analyze ambition in Lauren Kate's Fallen based on psychoanalytic approach. The object of this study is Fallen novel (2009) by Lauren Kate. This study is literary study, which can be categorized into a descriptive qualitative study. The researcher uses two data source: primary and secondary data sources. The primary data sources is Fallen novel by Lauren Kate and the secondary data sources are related to the primary data that support the analysis such as some books of psychology and website related to the research. The technique of data analysis is descriptive qualitative analysis. The result of this study shows that; firstly the structural elements of novel consist of character and characterization, setting, plot, point of view, style, and theme. Character and characterization in Fallen novel is Lucinda Price, Daniel Grigori and many more, setting is in Sword & Cross school. The point of view of Fallen novel, Kate uses third person. Plot consists of exposition, complication, climax, and resolution. Secondly, the psychoanalytic analysis of this novel shows that the ambition of Lucinda Price is to know more about Daniel Grigori Luce's love and she also has big ambition to find out Daniel's family background and to know if Daniel is her only true love.